PENGARUH GREEN PRODUCT DAN GREEN BRAND AWARENESS TERHADAP GREEN PURCHASE INTENTION - Hernizar, Anggry Tri; Ramdan, Asep Muhamad; Mulia, Faizal (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to study the effect of green products and green brand awareness on green purchase intentions. The variables used in this study are green product (x1) and green brand awareness (x2) as the independent variable and green purchase intention (y) as the dependent variable. This research uses quantitative methods using associative methods. Using questionnaires distributed to 150 respondents. The data analysis technique used is multiple linear regression analysis. The results obtained show a significant significance between green products and green brand awareness of green purchase intentions based on the results of simultaneous and partial hypothesis testing.